Laboratory diagnosis of chronic kidney disease in adults: an overview of hospitals inserted in the Portuguese National Health System - Natália R. Costa; Ana R. M. Carvalho; Carla M. A. Pinto; Adagmar Andriolo; Isabel C. Guerra (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Introduction: The laboratory diagnosis of chronic kidney disease (CKD) is a simple and cost-effective procedure that allows the detection of early stages of the disease, which is essential to avoid kidney damage and a life threateaning event. It consists of measuring serum creatinine concentration, urinary albumin concentration and calculating the estimated glomerular filtration rate (eGFR). In 2012, the guidelines for laboratory evaluation of the CKD were published by the Kidney Disease: Improving Global Outcomes (KDIGO). Objectives: This study aimed to evaluate whether the laboratories in hospitals of the Portuguese National Health System follow these guidelines and provide a correct diagnosis of CKD. Material and method: A questionnaire composed of 32 questions was sent to the Clinical Pathology Services of all hospitals inserted in the System. Results: All 49 labs responded that measure serum creatinine, 18 reported measurering eGFR. Ten reported measuring eGFR only if specifically ordered. Forty-four measure total protein and albumin in the urine, three only protein, one albumin alone, and one measure none of them. The type of samples, methods, reagents, equipment, expression units of results and reference intervals varied. Conclusion: There is great variability among laboratories in relation to the methodology of measuring serum creatinine, albumin and total protein in the urine. There are wide variations in the release of results. Most laboratories do not follow the guidelines recommended by the KDIGO 2012. This work indicates that there is a need to develop education and alignment processes in the laboratory diagnosis of CKD in the laboratories installed in hospitals inserted in the Portuguese National Health System.